A critical appraisal on the procedures of arrest in the syariah criminal procedure enactment (state of Selangor) 2003 with special references to the offence of close proximity / Fardiana Haryanti Ahmad Razali, Khairunnisa Khalid and Mohd Azhan Nazli - Ahmad Razali, Fardiana Haryanti; Khalid, Khairunnisa; Nazli, Mohd Azhan (2007)
This research is a critical analysis on arrest procedures of khalwat offenders in Malaysia. Arrests of khalwat offenders were thoroughly elaborated with references to the Syariah Criminal Procedure Enactment (State of Selangor) 2003 and the Islamic procedures of arrest. The procedures of arrest contained within the Enactment were also meticulously criticized and commented. In addition to arrest procedures within the Syariah Criminal Procedure Enactment, arrest procedures within the Criminal Procedure Code (Act 593) were also elaborated and compared. Apart from the evaluation of statutory procedures, histories of arrest procedures in Malaysia and the European medieval period were also emphasized. Issues interrelated with arrest of khalwat offenders such as the issue of spying was also explained apart form summarization of article that reflects weaknesses of arrest procedures involving khalwat offender. It was observed in this research study that there are many lacunas, uncertainties, and incomprehensiveness in arrests procedures within the Syariah Criminal Procedure Enactment (State of Selangor) 2003. It is hoped that the recommendations within this research would be implemented to improve and overcome the weaknesses of the Enactment. It is also hoped that the recommendation will be able to harmonize the differences of the two statutes, and the provisions of the Enactment with the teachings of Islam.